2014
DOI: 10.1186/1475-2875-13-246
|View full text |Cite
|
Sign up to set email alerts
|

Use of proscribed chloroquine is associated with an increased risk of pfcrt T76 mutation in some parts of Ghana

Abstract: BackgroundAfter years of disuse of chloroquine (CQ) as first-line anti-malarial drug in Ghana, reports from molecular studies conducted in parts of the country indicate varying prevalence of T76 mutation in the pfcrt gene. This situation has several health implications, one being that mutations that confer resistance to CQ have been reported to show substantial cross-resistance to other anti-malarial drugs. It is important to identify some of the factors contributing to the continuous presence of CQ resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…One of the most negative effects of self-medication is the selection of drug-resistant microorganisms. 11 It has previously been shown that the availability and use of CQ is linked to high prevalence of pfcrt mutant alleles, 23 and that withdrawal of CQ has been associated with the reduction of CQresistant parasites. 24 The frequencies of CQ-susceptible parasites as high as 91% were recently reported in samples from countries of Africa where CQ use was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most negative effects of self-medication is the selection of drug-resistant microorganisms. 11 It has previously been shown that the availability and use of CQ is linked to high prevalence of pfcrt mutant alleles, 23 and that withdrawal of CQ has been associated with the reduction of CQresistant parasites. 24 The frequencies of CQ-susceptible parasites as high as 91% were recently reported in samples from countries of Africa where CQ use was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) from January to December 2012. These districts have been shown to harbor parasites with varying drug resistance susceptibilities [ 19 ] and a parasite prevalence ranging from 11.4 to 15.4% [ 20 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized paired archived filter paper blood blots and serum samples from 95 volunteers who had been confirmed as P. falciparum positive at the three district hospitals in a larger study conducted in 2012 and previously reported by Asare et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral whole blood samples used for dried filter paper blood blots, thick and thin blood smears and harvesting of serum were collected from each participant as part of a larger study from three districts in the Central Region of Ghana [ 24 ]. The hemoglobin concentrations of the blood samples were measured directly using automated blood analyzers in the various study hospitals.…”
Section: Methodsmentioning
confidence: 99%